Rape: From Lucretia to #MeToo - Sanyal, Mithu M. (Verso, 2019)
Cover Page; Halftitle Page; Title Page; Copyright Page; Contents; Introduction; 1. Sex: No Means Yes, No Means No!; 2. A Fate Worse Than Death: Honor and Honesty; 3. The Aftermath: Trauma and Healing; 4. Black-and-White Thinking; 5. Omissions: Men, Masculinity, and Myths; 6. Missions: Yes Means Yes; Afterword: Notes from the Road; Bibliography; Notes; Index